Répartition des foraminifères benthiques dans les gisements de surface du Miocène d'Aquitaine (SW de la France) - Cahuzac, Bruno (2010)
The Aquitaine Basin (southwestern France) is known since long ago for its richness in marine miocene deposits of various facies. A few stratotypes concerning this period have been described in the investigated area. The stratigraphical framework has been recently revised and the study of new exposures completes our knowledge on these levels. In the present work, the authors produce a biostratigraphical distribution of about 160 species (larger and smaller foraminifera), found in the surface exposures of Aquitaine, from the topmost Oligocene (Chattian) through to Middle Miocene (including Serravallian). As a rule, the common species without significant ranges have not bcen mentioned. The microfaunas of several exposures have been thoroughly revised, which has allowed to precise the distribution of many species and induced a few modifications of the results previously produced. Synonymy problems and new taxonomical revisions have been taken into account. Of course, this work will be probably submitted to some changes according to new research on the already known exposures or other more recently discovered.